ANALISIS PENGARUH INOVASI PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP PEMBELAJARAN DI SEKOLAH DASAR PADA ERA REVOLUSI INDUSTRI 4.0 - Pertiwi, Putri Indah; Agustini, Silvia; Nurhakim, Yuga Fibra (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
In carrying out the learning process, there must be innovation in learning that will later support the learning process. This learning innovation is very important in learning because if there is no innovation then learning will not be interesting and seem boring. This study aims to determine how the influence of TGT (Teams Games Tournament) learning innovations on learning in elementary schools in the era of the Industrial revolution 4.0. This research uses qualitative methods, data collection by literature study, which will later take references from books, national and international journals, articles, and some of them. This learning innovation is very much needed in the learning process in elementary school because with innovation learning will seem interesting, learning will also be easily understood by students in elementary school, elementary school also definitely needs innovation because it can be seen that elementary school students are easy to get bored, and in the revolution era Industry 4.0 certainly requires learning innovation in order to adapt to existing changes.